2018
DOI: 10.1080/07391102.2018.1477622
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent dynamics in highly homologous adenylate kinases

Abstract: To correlate the structural features of enzymes to temperature adaptation, we studied psychrophile, mesophile, and thermophile adenylate kinases as model enzymes using bioinformatics and computational tools. Phylogenetic analysis revealed that mesophile and thermophile variants are clustered in one stem of phylogenetic tree and are close to contemporary time, while psychrophile enzyme is more close to their common ancestor. This finding is in good agreement with the process of environmental changes from ice ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…However, others have argued that these dynamical effects are short‐ranged (less than 6 Å) and cannot include the scaffold [5,44] . Alternatively, others suggested that the evolutionary advantage of dynamical and conformational flexibility in proteins was to accommodate different reaction mechanisms in the active site, [45,46] which enables catalytic promiscuity and facilitate the evolution of new proteins and functions [47–53] . Finally, some refer to the process by which protein dynamics influence protein activity as dynamic allostery, in analogy with allosteric regulation of protein activity upon the binding of a drug or toxin [54–56] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, others have argued that these dynamical effects are short‐ranged (less than 6 Å) and cannot include the scaffold [5,44] . Alternatively, others suggested that the evolutionary advantage of dynamical and conformational flexibility in proteins was to accommodate different reaction mechanisms in the active site, [45,46] which enables catalytic promiscuity and facilitate the evolution of new proteins and functions [47–53] . Finally, some refer to the process by which protein dynamics influence protein activity as dynamic allostery, in analogy with allosteric regulation of protein activity upon the binding of a drug or toxin [54–56] .…”
Section: Introductionmentioning
confidence: 99%
“…We assess electrostatic preorganization and structural dynamics effects by comparing the wild type (WT) to four AdK mutants engineered with entropy tuning mutations (to Gly) at distal sites [68] . Mutation to glycine at surface exposed sites were shown to be frequent in enzymes operating at cold temperatures, suggesting that dynamic allostery controls protein adaptation to the environment [50,68] . In the context of AdK, the mutants Ala37Gly, Ala55Gly, Val135Gly and Val142Gly (Figure 1) were shown experimentally to yield higher affinity or turnover than AdK WT, primarily due to changes in the flexibility of LID and AMPb structural domains [63,68] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations